Apigenin protects against ischemic stroke by increasing DNA repair - Ping, Niu; Zuo, Kuiyang; Cai, Jiahan; Rong, Chunshu; Yu, Ziqiao; Zhang, Xu; Wang, Gaihua; Ma, Chunyu; Yang, Huirong; Li, Jinhua; Wang, Xu; Zhao, Dexi (Frontiers in Pharmacology, 2024)
Abstract: Background and Objective. Oxidative stress is an important pathological process in ischemic stroke (IS). Apigenin (APG) is a natural product with favorable antioxidative effects, and some studies have already demonstrated the antioxidative mechanism of APG in the treatment of IS. However, the mechanism of APG on DNA damage and repair after IS is not clear. The aim of this study was to investigate the mechanism of APG on DNA repair after IS. Methods. Male Sprague-Dawley rats were used to establish a model of permanent middle cerebral artery occlusion (pMCAO) on one side, and were pre-treated with gavage of APG (30, 60, or 120 mg/ kg) for 7 day. One day after pMCAO, the brain tissues were collected. Cerebral infarct volume, brain water content, HE staining and antioxidant index were analyzed to evaluated the brain damage. Molecular Docking, molecular dynamics (MD) simulation, immunohistochemistry, and western blot were used to explore the potential proteins related to DNA damage repair. Results. APG has a low binding score with DNA repair-related proteins. APG treatment has improved the volume of cerebral infarction and neurological deficits, reduced brain edema, and decreased parthanatos and apoptosis by inhibiting PARP1/AIF pathway. In addition, APG improved the antioxidative capacity through reducing reactive oxygen species and malondialdehyde, and increasing glutathione and superoxide dismutase. Also, APG has reduced DNA damage- and cell death-related proteins such as PARP1, γH2A.X, 53BP1, AIF, cleaved caspase3, Cytochrome c, and increased DNA repair by BRCA1 and RAD51 through homologous recombination repair, and reduced non-homologous end link repair by KU70. Conclusions. APG can improve nerve damage after IS, and these protective effects were realized by reducing oxidative stress and DNA damage, and improving DNA repair.